2021
DOI: 10.18805/ijar.b-4228
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on Distribution of Sebaceous and Sweat Glands in Skin of Different Domestic Animals

Abstract: Background: Skin is the largest organ of the body, accounting for 15-20% of the total body weight and acts as a barrier between the external and internal environment and maintain homeostasis.The sweat and sebaceous glands in dermis of skin play vital role in developing the adaptive ability to the heat stress. Besides this, the distribution pattern and number of these glands vary in different animals that may aid in identification of different species.Methods: The study was conducted on abdominal skin of 36 adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…This study found mean density of 2.00 HF per mm 2 , matching the results by Debbarma et al ( 20 ) and Raheem, Elias and Ahmed ( 18 ), who indicate hair density in buffaloes of 1.91 and 2.78 HF per mm 2 , respectively. However, the number of HF in the literature varies, with values ranging from 91.84 cm −2 for Murrah animals ( 86 ), 135–145 cm −2 for Mediterranean buffaloes ( 17 ), and 394 cm −2 for Egyptian buffaloes ( 15 ). In fact, the lower hair density of buffaloes may have a double effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study found mean density of 2.00 HF per mm 2 , matching the results by Debbarma et al ( 20 ) and Raheem, Elias and Ahmed ( 18 ), who indicate hair density in buffaloes of 1.91 and 2.78 HF per mm 2 , respectively. However, the number of HF in the literature varies, with values ranging from 91.84 cm −2 for Murrah animals ( 86 ), 135–145 cm −2 for Mediterranean buffaloes ( 17 ), and 394 cm −2 for Egyptian buffaloes ( 15 ). In fact, the lower hair density of buffaloes may have a double effect.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the greater the gland activity at a given moment, the higher the possibility of the sweat produced being secreted, favoring the reduction of the skin ST. To the best of our understanding, such information is a first since no reference values were found in the literature to compare those variables. The recent studies have assessed the type and diameter of sweat ( 20 ) and sebaceous ( 21 ) glands in different regions of the body of buffaloes, in addition to their distribution ( 86 ); however, with no mention of the percentage of gland area, which is an indicative of activity of the respective glands.…”
Section: Discussionmentioning
confidence: 99%
“…Within the skin layers are sweat glands and sebaceous glands. The number and distribution of skin glands play a role in the adaptive ability of the skin to heat stress (Raghav et al, 2021). Sweat glands bring water to the skins surface to aid in the evaporative path of heat loss (i.e., SR) and each hair follicle is associated with a sebaceous gland, which releases sebum to protect against destructive agents and assists in heat tolerance (Saxena et al, 1994;Berman, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Sebaceous glands are part of the pilosebaceous unit and, as such, are distributed throughout the haired skin and mucocutaneous junctions of dogs and cats [1]. They are multilobulated, alveolar glands under hormonal influence [2][3][4] that produce lipid-rich sebum, which is essential for epidermal barrier function.…”
Section: Introductionmentioning
confidence: 99%